Essay. The Vicious Circles of Bureaucratic Circular Economy: The Case of Packaging Waste Euro-Targets for Romania - Octavian-Dragomir Jora; Alexandru Pătruți; Mihaela Iacob (Amfiteatru Economic)
The “circular economy” package put forward by the European Commission in 2015 is an ambitious plan in the area of environmental protection. The aim of this legal framework is to replace what is nowadays referred to as the “linear economy”, in which people consume and throw away, with an economic system which supposedly reuses all its available resources. In spite of its probably good intentions, the circular economy package contains at least one directive which under current economic conditions is practically inapplicable in countries such as Romania. The packaging waste directive, which we speak of, focuses on raising mandatory recycling rates above the current levels. Past experience has shown that the present recycling system in Romania was unable to fulfil even the exiting, more modest targets. The lack of a necessary infrastructure in waste management and collection, combined with poor legislative measures made fulfilling individual environmental obligations a real challenge for producers of packaged goods. All the more, the recycling targets increase, without being correlated with the other conditions required for their completion, would place an undue burden on producers, that would also trigger a significant rise in consumer prices, especially in the area of foodstuff products.